EFEKTIVITAS JAMUR Rhizoctonia binukleat TERHADAP PENERKEMBANGAN PATOGEN BUSUK BATANG VANILI (Fusarium oxysporum f.sp. vanillae) SECARA IN VITRO - Haryuni Haryuni; Teguh Supriyadi; Tyas Soemarah K. (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2014)
Fusarium oxysporum f.sp. vanillae is a pathogenic fungi for vanili plants. The fungi have chitin cell wall that can be degraded by chitinase from chitinolytic Rhizoctonia binucleate of fungi. Aim of this research was determine how the interaction between the F. oxysporum f.sp. vanillae and Rhizoctonia binucleate were isolated from plant rizosfere. Chitinolytic activity were measured based on the clear zone around the colony in chitin medium. Interaction of fungi were determined by an antagonistic test. This research showed that Rhizoctonia binucleate is chitinolytic, antagonist and alternative of biofungiside to F.oxysporum f.sp. vanillae.